2016
DOI: 10.5222/terh.2016.041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rejection causes based from preanalytic origin in our emergency laboratory

Abstract: ÖZAmaç: Laboratuvardaki toplam hataların büyük çoğunluğunu preanalitik evre hataları oluşturur (%46-68). Bu çalışmanın amacı, acil laboratuvarımızdaki bazı test gruplarına ilişkin reddedilen örneklerin oranlarını ve nedenlerini araştırmaktı. Yöntem: Çalışma Kasım 2014 ve Nisan 2015 tarihleri arasında reddedilen örnekler üzerine planlandı ve acil laboratuvarındaki 6 test grubu (klinik kimya, ilaç düzeyi, kardiyak belirteçler, koagülasyon, eritrosit sedimantasyon hızı, tam idrar tetkiki) dâhil edildi. Numuneleri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…After the training, a significant enhancement observed in the rates of these two errors, but no improvement/decrease seen in other ones. In the study performed by Aksit et al (20) in our hospital, it has been reported that the most common cause of preanalytical errors was the test request errors and the training of medical secretaries could solve this problem. The main reasons for ‘test request errors’ which was found to have been the most reject rate in our study were observed such as: the codes of the parameters used in our hospital’s emergency laboratory had diversity, test requests coming from services and intensive care units during out of working hours were being putting in process by the secretaries working in emergency services, appointment of medical secretaries in emergency laboratories who were employed in different departments, who were newly employed or who did not have a HIS training.…”
Section: Discussionmentioning
confidence: 92%
“…After the training, a significant enhancement observed in the rates of these two errors, but no improvement/decrease seen in other ones. In the study performed by Aksit et al (20) in our hospital, it has been reported that the most common cause of preanalytical errors was the test request errors and the training of medical secretaries could solve this problem. The main reasons for ‘test request errors’ which was found to have been the most reject rate in our study were observed such as: the codes of the parameters used in our hospital’s emergency laboratory had diversity, test requests coming from services and intensive care units during out of working hours were being putting in process by the secretaries working in emergency services, appointment of medical secretaries in emergency laboratories who were employed in different departments, who were newly employed or who did not have a HIS training.…”
Section: Discussionmentioning
confidence: 92%
“…In studies conducted in Turkey, there are studies in which the sample rejection rate ranges from 1 to 1.30% (17,18,30,31). There are also studies where the rejection rate is between 0.3% and 0.7% (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…In the study, it was observed that the vacuum system, which draws blood to a sufficient level, is not common, especially in services. It is known that the risk of hemolysis also increases, as the risk of blood entering the injector hitting the wall of the tube with pressure increases due to the absence of a vacuum system (17). In this context, the identified improvement activities are presented in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation